CaII, YbII and SmII Bis(Amido) Complexes Coordinated by NHC Ligands: Efficient Catalysts for Highly Regio‐ and Chemoselective Consecutive Hydrophosphinations with PH3. Issue 2 (11th December 2018) - Lapshin, Ivan V.; Basalov, Ivan V.; Lyssenko, Konstantin A.; Cherkasov, Anton V.; Trifonov, Alexander A.
Abstract: The first example of intermolecular hydrophosphination of styrene, 2‐vinylpyridine and phenylacetylene with PH3 catalyzed by bis‐(amido) complexes [(Me3 Si)2 N]2 M(NHC)2 (M=Ca, Yb, Sm) coordinated by NHC ligands is described. The reactions of styrene with PH3 proceed under mild conditions in quantitative yields to afford only anti‐Markovnikov product and allow for the chemoselective synthesis of primary, secondary and tertiary phosphines. Addition of phenylacetylene to PH3 regardless the initial molar substrates ratio results in the exclusive formation of a tertiary tris‐(Z‐styryl)‐phosphine. Crucial effect of the Lewis base coordinated to the metal ion in precatalyst on catalytic activity in styrene hydrophosphination with PH3 was demonstrated. Free NHCs were also found to be able to promote addition of PH3 to styrene, however they provide much lower reaction rates compared to the metal complexes. Abstract : Any phosphine you like : The first example of intermolecular hydrophosphination of styrene, 2‐vinylpyridine and phenylacetylene with PH3 catalyzed by Ca II, Yb II and Sm II bis(amido) complexes coordinated by NHC ligands is described. The reactions of styrene with PH3 proceed under mild conditions in quantitative yields to afford only anti‐Markovnikov product and allow for the chemoselective synthesis of primary, secondary and tertiary phosphines.